2015
DOI: 10.3329/bjp.v10i4.24153
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of anticonvulsant, antimicrobial and hemolytic activity of <i>Aitchisonia rosea</i>

Abstract: <p class="Abstract">The purpose of this study was to evaluate the anticonvulsant, antimicrobial and hemolytic effect of <em>Aitchisonia rosea</em>. The anticonvulsant effect was studied at doses 400 and 800 mg/kg against pentylenetetrazole, strychnine and picrotoxin-induced seizures in albino mice. The antimicrobial assay was conducted by disc diffusion method and minimum inhibitory concentration. Hemolytic effect was analyzed by reported method. Phenolic compounds present in the n-butanol fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 22 publications
1
4
0
Order By: Relevance
“…ARME significantly and dose dependently decreased the paw licking time in second phase that might be owing to the inhibition of inflammatory mediators, so it acts more like NSAIDs in reducing pain. Accordingly, current findings have avowed that crude extract of Aitchisonia rosea possess preeminent potential to alleviate inflammation accompanied by algesia and may be allied to the presence of various phytoconstituents, as have been earlier reported in Aitchisonia rosea i.e., alkaloids, terpenoids, flavonoids, tannins and phenolics (quercetin, caffeic acid, chlorogenic acid and syringic acid) [4]. In addition, free radical scavenging and reducing potential of Aitchisonia rosea has previously been measured by using DPPH and reducing power assay [5].…”
Section: Discussionsupporting
confidence: 54%
See 3 more Smart Citations
“…ARME significantly and dose dependently decreased the paw licking time in second phase that might be owing to the inhibition of inflammatory mediators, so it acts more like NSAIDs in reducing pain. Accordingly, current findings have avowed that crude extract of Aitchisonia rosea possess preeminent potential to alleviate inflammation accompanied by algesia and may be allied to the presence of various phytoconstituents, as have been earlier reported in Aitchisonia rosea i.e., alkaloids, terpenoids, flavonoids, tannins and phenolics (quercetin, caffeic acid, chlorogenic acid and syringic acid) [4]. In addition, free radical scavenging and reducing potential of Aitchisonia rosea has previously been measured by using DPPH and reducing power assay [5].…”
Section: Discussionsupporting
confidence: 54%
“…It was then filtered using Whattman filter paper. The Aitchisonia rosea methanol extract (ARME) was concentrated and kept at 4 °C in a refrigerator [4].…”
Section: Collection and Extraction Of Plantmentioning
confidence: 99%
See 2 more Smart Citations
“…Hence, it will be essential to pay attention to traditional medicine and herbal medicines to achieve low-risk drugs with minimal side effects (Rostampour et al, 2014). The plants such as Aitchisonia rosea (Rasool et al, 2015), Bacopa monnieri (Paulose et al, 2008), Cannabis sativa (Leite and Carlini, 1973), Cyperus articulates (Bakanova and Leutskií, 2971), Sechium edule (Mumtaz et al, 2012), Silybum marianum (Waqar et al, 2016) and Zizyphus jujube (Puhaja et al, 2011) showed antiepileptic effect. (Wan et al, 2017), and sedative (Amos et al, 2003) effects in animal models.…”
Section: Introductionmentioning
confidence: 99%